Dispute settlement of land certificate blocking at the national land agency through a notarial peace deed - Herdiawati, Wina (The International Journal of Politics and Sociology Research, 2024)
The recording of land blocking at the National Land Agency can occur due to an act, legal event or a land dispute or conflict. Through a peace agreement that has been agreed between the parties to the dispute, a deed of peace is made. Peace deeds made by the parties before a notary can be an effective and efficient choice in resolving disputes arising from civil legal relations that occur outside the court. This research uses normative juridical research methods, namely research focused on examining the application of positive legal norms relating to the validity of an agreement. The data collection technique used is using literature study. The analysis in this research uses qualitative analysis. Notaries carry out part of the state's power in the field of civil law to serve the interests of people who need legal evidence in the form of authentic deeds recognized by the state as perfect evidence. The notary peace deed becomes a dispute resolution and can provide justice as well as legal certainty between the parties to the dispute.